Case Report: Rapid progression following fertility-sparing management of high-grade endometrial carcinoma - Qilin, Wang; Yang, Liu; Junqiang, Li; Shengying, Yang; Yong, Luo (Frontiers in Medicine, 2025)
Endometrial cancer (EC) is a common gynecologic malignancy with a rising incidence in young women. While fertility-preserving progestin therapy is an option for early-stage, well-differentiated (Grade 1, FIGO IA) tumors, its efficacy in poorly differentiated (Grade 3) tumors remains controversial due to their aggressive nature and high recurrence rates. In this study, we report a 26-year-old nulliparous woman with Grade 3 endometrioid adenocarcinoma (FIGO IA) who underwent medroxyprogesterone acetate (MPA, 160 mg/day) therapy and three hysteroscopic biopsies within 10 months, each showing no residual malignancy. Shortly after the last hysteroscopy, she developed a rapidly enlarging adnexal mass, and imaging revealed extensive peritoneal metastases. Laparoscopic exploration confirmed widespread tumor dissemination, and despite paclitaxel plus cisplatin (TP regimen) chemotherapy, the disease progressed rapidly, demonstrating chemoresistance. She declined further treatment and succumbed to the disease within months. This case highlights the potential limitations and challenges of fertility-sparing treatment in high-grade endometrial carcinoma, even in FIGO IA stage, and underscores the importance of strict adherence to current selection criteria and thorough risk assessment. Additionally, it raises concerns about the potential role of repeated hysteroscopic procedures in tumor dissemination, particularly with high intrauterine pressure. Given the poor prognosis of Grade 3 endometrial carcinoma, early definitive surgery should be prioritized over conservative management. Further research is needed to evaluate the oncologic safety of repeated hysteroscopic procedures and explore alternative surveillance strategies.